Study Of Chemical Concentration Of Main Ingredients For Making Portland Composite Cement - Loth Botahala; Herianus Manimoy; Yuwinta Erlina Tonu Lema; Eflin Dollu Klaping; M. Tang (Widya Teknik, 2021)
This study aims to determine the concentration of the main raw material compounds of cement making before adding limestone additives and determining the compressive strength and porosity and water absorption of cement before adding limestone additives. The result showed that cement with the concentration of 3CaO.SiO2 = 96,9%; 2CaO.SiO2 = negative; 3CaO.Al2O3 = 4,4%; 4CaO.Al2O3.Fe2O3 = 9.7%. If added limestone additive then it will decrease the adhesiveness and create a very wide pore can make a building becomes fragile. Such concentrated cement can not withstand the reaction of other particles from the air.